Antigenotoxic effects of Mandevilla velutina (Gentianales, Apocynaceae) crude extract on cyclophosphamide-induced micronuclei in Swiss mice and urethane-induced somatic mutation and recombination in Drosophila melanogaster - Regildo Márcio Gonçalves da Silva; Neila Coelho de Sousa; Ulrich Graf; Mário Antônio Spanó (Genetics and Molecular Biology, 2008)
A Mandevilla velutina crude extract was investigated using the mouse micronucleus test (MNT) and the Drosophila melanogaster somatic mutation and recombination test (SMART) using standard (ST) and high bioactivation (HB) crosses. The MNT used 10 mg, 20 mg or 40 mg per 100 g of body weight (bw) of extract with and without 0.2 mg per 100 g bw peritoneal cyclophosphamide. There was no genotoxicity in the negative control or extract only groups and, compared to the cyclophosphamide control, there was a significant reduction in micronucleated polychromatic erythrocytes in all the groups given extract plus cyclophosphamide. For SMART larvae were fed 5 or 10 mg mL-1 of extract for seven days with and without 0.89 mg mL-1 of urethane given on day seven. The ST and HB flies showed no significant differences in spots between the negative control and the extract only groups. The number of urethane-induced spots was reduced by the highest concentration of extract for the ST flies and by both concentrations of extract for the HB flies. The results suggest that M. velutina extract is not genotoxic but is antigenotoxic.